NEEDS ANALYSIS OF MULTIBALL EXERCISE METHODS TOWARDS THE IMPROVEMENT OF BACKHAND DRIVE SKILL ON BEGINNER TABLE TENNIS ATHLETES - Bessy Sitorus Pane; James Tangkudung; Abdul Sukur (Program Pascasarjana Universitas Negeri Jakarta, 2019)
This study aims to determine the needs for table tennis multi-ball training for table tennis practice participants at the Table Tennis Association (Persatuan Tenis Meja; abbr.: PTM) in Medan. This research uses a descriptive qualitative method. Subjects were 20 beginner athletes aged 16-21 years. The research was conducted at PTM Garuda Medan. The results show that 85% of table tennis exercises are in demand. 75% of exercises are done three times a week, 90% stated the duration of training is 90-120 minutes, and 80% deem the exercise sufficient. 86% agreed to be given multi-ball training, 91% agreed to be given specialized training distributed multi-ball practice, 89% agreed the role of the trainer in training activities, 71% answered the trainer provided variations in backhand drive training, 89% agreed the trainer gave the method of multi-ball distributed practice. 87% believe that multi-ball training can improve backhand drive skills, 91% agree that exercise-based variations are given drill-based, and 65% agree given ball feeling games for exercise variations. 89% agree that drills use targets, 60% agree with media, 75% agree agreed given the variation of multi-ball training, and 83% agreed given the drill for backhand drive skills with the multi-ball training method.